Partnering as a Research Organization: a Balancing Act - Faling, Marijn (2018)
Although partnerships are believed to tackle most pressing societal challenges such as climate change and food security, they usually come with various challenges like illustrated in this article on the work of CCAFS. The interviews with Bruce Campbell, CCAFS Program Director, and Philip Thornton, CCAFS Flagship Leader and Principal Scientist, highlight the balancing act when a research organization engages in partnerships. CCAFS research organizations have to dedicate resources to building partnerships without losing focus on actual research, loosen their standards without compromising reputation, and meet targets without skimping on the more complex and longer-term activities.